New minimally invasive technique for cystoscopic laser treatment of fetal ureterocele. (30th May 2017) - Persico, N.; Berrettini, A.; Fabietti, I.; Dallagiovanna, C.; Minoli, D.; Mosca, F.; Fedele, L.; Manzoni, G.
Abstract: Prenatal ultrasound detection of fetal ureterocele with bilateral hydroureteronephrosis, obstruction of the bladder outlet and progressive amniotic fluid reduction have been associated with a significant risk of end‐stage chronic renal disease after birth. Fetal cystoscopic laser incision of the ureterocele, using standard 3.5‐mm fetoscopic access to the amniotic cavity and the fetal bladder with the aim of relieving the bladder outflow obstruction to preserve renal function, has been reported previously in a case with a favorable outcome. We report on two additional cases of fetal ureterocele treated by cystoscopic laser decompression. In the first case, a standard 3.3‐mm uterine entry was used. In the second case, a new approach was adopted using an 'all‐seeing needle' 1.6‐mm endoscope. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.